Life beyond the camp : rethinking return, reconstruction and women's expression of lived experiences in Northern Uganda - Frérotte, Naomi (2015)
The conflict in Northern Uganda is recognized as having come to an end with the signing of a cessation of hostilities agreement between the Lord’s Resistance Army and the Government of Uganda in August 2006, which resulted in improved security. Estimates suggest that the majority of the displaced populations have left their camps and moved either to transit sites near farms or to their village of origin. Much research has been done on the living conditions of women in the Ugandan IDP camps yet very little has been written on the situation for women who return home or resettle after the camp.